Modeling Malaysia Debt Threshold: Debt Composition (Domestic Debt; External Debt; Household Debt) - Kueh, Jerome; Liew, Khim Sen; Yong, Sze Wei; Lau, Evan; Liwan, Audrey (Universiti Malaysia Sarawak (UNIMAS), 2017)
Malaysia as one of the fast growing economy in the Southeast Asia region experienced challenging tasks in managing the increasing level of debts. This study intends to investigate the implication of the debt (domestic debt, external debt and household debt) towards economic growth of Malaysia by adopting Threshold regression method for sample period from 1980 to 2015. Empirical findings indicate that the threshold level for domestic debt is approximately 47% of GDP, 17% of GDP for external debt and 81% of GDP for household debt where there is a negative impact on growth the debt is above the threshold level.